Tools Expert Choice Dalam Implementasi Metode Analytical Hierarchy Process (AHP) Untuk Penseleksian Kurir Baru - Nunu Kustian; Siti Julaeha (Universitas Indraprasta PGRI, 2022)
Westbike Messenger Service (WMS) is a company engaged in courier services in delivering packages for individuals and companies that use bicycles, but in the process of accepting candidates and courier selection with file collectors as requirements and direct interviews. To simplify the process, a decision system is needed to support the selection of new couriers using the Analytical Hierarchy Process (AHP) method, so that the results are obtained that the system built can be used by the WMS recruitment department according to the criteria required by several candidate names as an alternative to be calculated and obtained the best courier candidates to be accepted by the WMS company.